(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. In recent years, many countries have tried to incorporate the probability concepts into the curriculum of primary school. The researchers disagree as to what the age of children dealing with probability contents should be. The aim of this study was to investigate the grade of understanding of the probability concepts in primary school students depending on their age and their gender. It has been concluded that the majority of students was able to recognize different events and categorize them depending on their likelihood. The major difference in their abilities was noticed between the children of the second grade and those of the third grade whereas it has been experienced that girls performed better in all the tasks and in all the grades except for the fourth grade in which boys present a slightly better score.